A meta-analysis of the reproducibility of food frequency questionnaires in nutritional epidemiological studies - Qi Cui; Yang Xia; Qijun Wu; Qing Chang; Kaijun Niu; Yuhong Zhao (BMC, 2021)
Abstract Background Reproducibility of FFQs measures the consistency of the same subject at different time points. We performed a meta-analysis to explore the reproducibility of FFQs and factors related to reproducibility of FFQs. Methods and findings A systematic literature review was performed before July 2020 using PubMed and Web of Science databases. Pooled intraclass and Spearman correlation coefficients (95% confidence interval) were calculated to assess the reproducibility of FFQs. Subgroup analyses based on characteristics of study populations, FFQs, or study design were performed to investigate factors related to the reproducibility of FFQs. A total of 123 studies comprising 20,542 participants were eligible for the meta-analysis. The pooled crude intraclass correlation coefficients ranged from 0.499 to 0.803 and 0.499 to 0.723 for macronutrients and micronutrients, respectively. Energy-adjusted intraclass correlation coefficients ranged from 0.420 to 0.803 and 0.507 to 0.712 for macronutrients and micronutrients, respectively. The pooled crude and energy-adjusted Spearman correlation coefficients ranged from 0.548 to 0.851 and 0.441 to 0.793, respectively, for macronutrients; and from 0.573 to 0.828 and 0.510 to 0.744, respectively, for micronutrients. FFQs with more food items, 12 months as dietary recall interval (compared to less than 12 months), and a shorter time period between repeated FFQs resulted in superior FFQ reproducibility. Conclusions In conclusion, FFQs with correlation coefficients greater than 0.5 for most nutrients may be considered a reliable tool to measure dietary intake. To develop FFQs with higher reproducibility, the number of food items and dietary recall interval should be taken into consideration.